1987
DOI: 10.1051/rnd:19870401
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenèse des hormones de l'axe somatotrope

Abstract: Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1995
1995

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Pre viously, we presented the first ultrastructural and immu nocytochemical data on the differentiating capacity of Rathke's pouches (from fetal day 11) in a serum-free, anti biotic-free culture model [31,32] and demonstrated that the explanted 11-to 13-dav-old Rathke's pouches display signs of functional differentiation exhibiting all specific hormone-containing cell types by the end of the 7-dayculture period. Several reports stated that the absence of hypothalamic neurohormones or other hormones after day 11 of fetal development prevents the functional dif ferentiation of lactotrophs and other pituitary cell types [33][34][35][36]. We also reported that immunocytochemically and radioimmunologically negative primordia start to synthesize specific hormones (LH, FSH, TSH) in the serum-free and antibiotic-free culture system and that they are able to enhance the rate of synthesis and the amount of stored or released hormones with the time in culture in a manner characteristic for a given hormone [22,37], The present data together with our previous observations suggest that the expression of PRL and other phenotypes occur and the specific differentiation pro ceeds even in isolated pituitary glands regulated by intrapituitary mechanisms, independently of extrapituitary chemical signals.…”
Section: Discussionmentioning
confidence: 99%
“…Pre viously, we presented the first ultrastructural and immu nocytochemical data on the differentiating capacity of Rathke's pouches (from fetal day 11) in a serum-free, anti biotic-free culture model [31,32] and demonstrated that the explanted 11-to 13-dav-old Rathke's pouches display signs of functional differentiation exhibiting all specific hormone-containing cell types by the end of the 7-dayculture period. Several reports stated that the absence of hypothalamic neurohormones or other hormones after day 11 of fetal development prevents the functional dif ferentiation of lactotrophs and other pituitary cell types [33][34][35][36]. We also reported that immunocytochemically and radioimmunologically negative primordia start to synthesize specific hormones (LH, FSH, TSH) in the serum-free and antibiotic-free culture system and that they are able to enhance the rate of synthesis and the amount of stored or released hormones with the time in culture in a manner characteristic for a given hormone [22,37], The present data together with our previous observations suggest that the expression of PRL and other phenotypes occur and the specific differentiation pro ceeds even in isolated pituitary glands regulated by intrapituitary mechanisms, independently of extrapituitary chemical signals.…”
Section: Discussionmentioning
confidence: 99%